Demostraciones
  1. Si $a \mid b$, entonces $b=aq$ con $q\in \mathbb{Z}$. Multiplicando la igualdad por $c$, $cb=a(cq)$ con $cq\in \mathbb{Z}$. Entonces, $a \mid bc$.
  2. Como $a \mid b$ y $a \mid c$, $b=aq$ y $c=ar$, con $q,r\in \mathbb{Z}$. Entonces $bc=(aq)(ar)=a^{2}(qr)$, $qr\in \mathbb{Z}$. Entonces $a^{2} \mid bc$.
  3. $a \mid b$ si y sólo si $b=aq$, $q\in \mathbb{Z}$. Como $c\neq 0$, $b=aq \Leftrightarrow bc=ac(q)$, y esto pasa si y sólo si $ac \mid bc$.
Unless otherwise stated, the content of this page is licensed under Creative Commons Attribution-ShareAlike 3.0 License